Association of ambient PM2.5 and its components with preeclampsia risk among pregnant women in a high-altitude region - Rui Li; Zhenjuan Li; Hanping Ma; Donghua Li; Xiong Yue; Xiaoshu Zhang; Tingrong Wang; Zixuan Zou; Tianshan Shi; Xiaowei Ren (Environmental Pollution, 2026)

Trait plasticity and drought thresholds in Artemisia ordosica during summer drought - Mingze Xu; Lei Ma; Cheng Li; Charles P.-A. Bourque; Manyi Li; Lizhen Zhang; Chuan Jin; Tianshan Zha (Plant and Soil, 2025)

Associations of ambient air pollution exposure to fine particulate matter and its chemical constituents before and during pregnancy with the risk of full-term small for gestational age: a retrospective cohort study - Tingrong Wang; Hanping Ma; Rui Li; Donghua Li; Tianshan Shi; Zhenjuan Li; Zixuan Zou; Xiaowei Ren (International Archives of Occupational and Environmental Health, 2025)

Spatiotemporal variation in carbon use efficiency derived from eddy-covariance measurement of global terrestrial biomes - Chuan Jin; Tianshan Zha; Charles P.-A. Bourque; Zehao Fan; Weirong Zhang; Kai Di; Yue Jiao; Qiaofeng Ma; Dongdan Yuan; Hongxian Zhao; Shaorong Hao; Yifei Lu; et al. (Agricultural and Forest Meteorology, 2025)

Retardation factor scaling for contaminant transport in fractured media - Sida Jia; Funing Ma; Zhijie Yang; Zhichao Zhou; Hui Ling; Tianshan Lan; Weiliang Wang; Yong Tian; Hung Vo Thanh; Mohamad Reza Soltanian; Zhenxue Dai (Advances in Water Resources, 2024)

Prenatal exposure to fine particulate matter chemical constituents and the risk of stillbirth and the mediating role of pregnancy complications: A cohort study - Tianshan Shi; Hanping Ma; Donghua Li; Li Pan; Tingrong Wang; Rui Li; Xiaowei Ren (Chemosphere, 2024)

Evolutionary game of end-of-life vehicle recycling groups under government regulation - Zhang Yu; Ma Tianshan; S. Abdul Rehman; Arshian Sharif; Laeeq Janjua (Clean Technologies and Environmental Policy, 2023)

The role of construction industry and construction policy on sustainable rural development in China - Xueying Wu; Tianshan Ma; Jinxi Zhang; Baixi Shi (Environmental Science and Pollution Research, 2023)

Evaluation of the vulnerability of a leaky aquifer considering the retardation effect of an aquitard for specific pollutants: case study in the Tongzhou Plain, China - Jinjie Miao; Zhen Ma; Hongwei Liu; Xu Guo; Yaonan Bai; Tianshan Lan; Fugang Wang; Yuqing Cao (Hydrogeology Journal, 2020)

Different Effects of Spring and Summer Droughts on Ecosystem Carbon and Water Exchanges in a Semiarid Shrubland Ecosystem in Northwest China - Peng Liu; Tianshan Zha; Xin Jia; T. Andrew Black; Rachhpal S. Jassal; Jingyong Ma; Yujie Bai; Yajuan Wu (Ecosystems, 2019)

Divergent long‐term trends and interannual variation in ecosystem resource use efficiencies of a southern boreal old black spruce forest 1999–2017 - Peng Liu; T. Andrew Black; Rachhpal S. Jassal; Tianshan Zha; Zoran Nesic; Alan G. Barr; Warren D. Helgason; Xin Jia; Yun Tian; Jilmarie J. Stephens; Jingyong Ma (Global Change Biology, 2019)
Long‐term trends in ecosystem resource use efficiencies (RUEs) and their controlling factors are key pieces of information for understanding how an ecosystem responds to climate change. We used continuous eddy covariance and microclimate data over the period 1999–2017 from a 120‐year‐old black spruce stand in central Saskatchewan, Canada, to assess interannual variability, long‐term trends, and key controlling factors of gross ecosystem production (GEP) and the RUEs of carbon (CUE = net primary production [NPP]/GEP), light (LUE = GEP/absorbed photosynthetic radiation [APAR]), and water (WUE = GEP/evapotranspiration [ E ]). At this site, annual GEP has shown an increasing trend over the 19 years ( p 2 concentration. Interannual variability in GEP, aside from its increasing trend, was most strongly related to spring temperatures. Associated with the significant increase in annual GEP were relatively small changes in NPP, APAR, and E , so that annual CUE showed a decreasing trend and annual LUE and WUE showed increasing trends over the 19 years. The long‐term trends in the RUEs were related to the increasing CO 2 concentration. Further analysis of detrended RUEs showed that their interannual variation was impacted most strongly by air temperature. Two‐factor linear models combining CO 2 concentration and air temperature performed well ( R 2 ~0.60) in simulating annual RUEs. LUE and WUE were positively correlated both annually and seasonally, while LUE and CUE were mostly negatively correlated. Our results showed divergent long‐term trends among CUE, LUE, and WUE and highlighted the need to account for the combined effects of climatic controls and the ‘CO 2 fertilization effect’ on long‐term variations in RUEs. Since most RUE‐based models rely primarily on one resource limitation, the observed patterns of relative change among the three RUEs may have important implications for RUE‐based modeling of C fluxes.